2013
DOI: 10.1603/ec12313
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Selected Insecticides and Risk Assessment in the Insect Egg Parasitoid <I>Trichogramma confusum</I> (Hymenoptera: Trichogrammatidae)

Abstract: The parasitoid Trichogramma confusum Viggiani (Hymenoptera: Trichogrammatidae) is an important natural enemy of many lepidopterans throughout the world. Extensive toxicological tests have clarified the toxic effects of insecticides on trichogrammatids, but only few studies have examined these effects on T. confusum. Among the seven classes of tested chemicals, organophosphates and carbamates exhibited the highest intrinsic toxicity to the parasitoid with LC50 values ranging from 0.037 (0.030-0.046) to 0.29 (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 48 publications
(69 reference statements)
0
8
0
1
Order By: Relevance
“…Opposite to He et al (2012) that proved the safety of systemic exposure to imidacloprid on S. japonicum, in this study systemic application of the field recommended concentration of thiamethoxam resulted in 100% death of S. japonicum within 24 h. Thiamethoxam is thought to have different mode of action than imidacloprid (Kayser et al, 2004) and it may be more toxic to natural enemies than imidacloprid, especially when applied systemically (Prabhaker et al, 2011;Wang et al, 2013;Wang et al, 2014). However, the opposite results were revealed by Al-Deeb et al (2001) and Youn et al (2003).…”
Section: Acute Toxicity Of Neonicotinoids On Natural Enemiesmentioning
confidence: 67%
See 1 more Smart Citation
“…Opposite to He et al (2012) that proved the safety of systemic exposure to imidacloprid on S. japonicum, in this study systemic application of the field recommended concentration of thiamethoxam resulted in 100% death of S. japonicum within 24 h. Thiamethoxam is thought to have different mode of action than imidacloprid (Kayser et al, 2004) and it may be more toxic to natural enemies than imidacloprid, especially when applied systemically (Prabhaker et al, 2011;Wang et al, 2013;Wang et al, 2014). However, the opposite results were revealed by Al-Deeb et al (2001) and Youn et al (2003).…”
Section: Acute Toxicity Of Neonicotinoids On Natural Enemiesmentioning
confidence: 67%
“…However, their environmental compatibility has recently come under scrutiny (European Commission, 2013;Goulson, 2013). Their toxicity risks to natural enemies have recently been heavily tested and the results indicated that the acute toxicity of field recommended concentrations of neonicotinoids varies from high to harmless (Tirello et al, 2013;Wang et al, 2013;Gontijo et al, 2014). The toxicity risk of neonicotinoids is affected by application methods (Pozzebon et al, 2011) as well as the natural enemy species (Roubos et al, 2014) and developmental stages under study (Rill et al, 2008).…”
Section: Acute Toxicity Of Neonicotinoids On Natural Enemiesmentioning
confidence: 99%
“…Residual toxicological tests of the eight insecticides (shown in Table ) were conducted on adults of E. formosa . Concentration–mortality response assays were carried out by exposing the parasitoid adults to the residues of five to seven concentrations of each tested insecticide . Moreover, the field recommended concentration of each insecticide was also tested.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Concentration-mortality response assays were carried out by exposing the parasitoid adults to the residues of five to seven concentrations of each tested insecticide. 39 Moreover, the field recommended concentration of each insecticide was also tested. Newly emerged (<8 h) E. formosa adults were collected and subjected to a residual toxicological test on an inert substrate.…”
Section: Acute Toxicity On Encarsia Formosa Adultsmentioning
confidence: 99%
“…A variação no parasitismo das espécies de Trichogramma expostas a um mesmo inseticida pode estar associada a diferentes níveis de tolerância das espécies aos inseticidas. A tolerância diferenciada pode ocorrer entre espécies de Trichogramma ou mesmo entre linhagens de uma mesma espécie (wu & Miyata 2005;Vianna et al 2009;alMeida et al 2010;wang et al 2013). Além disso, a formulação e a concentração do produto também podem afetam o parasitismo (pratissoli et al 2004).…”
Section: E-issn 1983-0572unclassified